The Continuing Adventures of the Dialectic: On Roland Boer's Socialism with Chinese Characteristics: A Guide for Foreigners. (25th March 2022) - Balasopoulos, Antonis
Abstract : This article begins by dwelling on the forms and causes of Western "historical nihilism" toward the Chinese socialist project. I then analyze issues attendant to Deng's appeal to "liberating thought, " particularly as regards the importance of the development of the forces of production and the dilemmas this presents for socialists. This segues into a discussion of contradiction analysis, which is theoretically central in Boer's book. Through the discussion of the difference of such analysis from forms of "either/or" logic dominant in the West, I arrive at the significance of the category of the "concrete universal" (Hegel) for the understanding of "socialism with Chinese characteristics." After unpacking some of the central issues posed by the "reform and opening-up, " I dwell on the question of socialism in China. I emphasize some of the complications inherent in the combination of socialist planning and the market economy, including the issue of the conception of a future or prospective "communist" stage. The discussion concludes by dwelling on issues of law and political structure, with particular emphasis on the innovative importance of "rule of law" in the socialist context, as well as on the importance of contradiction analysis for understanding the dialectic of sovereignty and globalization.